A Methodological Evaluation of Four Different Paired Associative Stimulation Paradigms in Healthy Controls - Kenan Hodzic; Magnus Thordstein; Joakim Strandberg; Elisabet Jerlhag; Caroline E. Wass (Brain Sciences)
Background/Objectives: Plasticity deficits play a key role in the pathophysiology of various psychiatric and neurological disorders. Paired associative stimulation (PAS) leverages Hebbian principles to induce synaptic plasticity in the human brain. By repeatedly pairing (1) the peripheral nerve stimulation of the median nerve with (2) transcranial magnetic stimulation over the primary motor cortex (M1) at different inter-stimulus intervals (25 ms; PAS-25, or 10 ms; PAS-10), corticospinal excitability can be increased (PAS-25, mimicking long-term potentiation (LTP)) or decreased (PAS-10, mimicking long-term depression (LTD)). However, variations in the number of pairings and inter-pair intervals lack consensus. The aim of the study was to evaluate four different PAS paradigms, i.e., PAS-10 and PAS-25 with both 180 versus 225 pairings each, to establish the most reliable PAS protocols for LTP- and LTD-like cortical changes. Methods: In a randomized, double-blind, crossover study, 14 healthy participants underwent PAS-10 and PAS-25 with 180 and 225 pairings. Excitability was assessed by quantifying the EMG response amplitude of a hand muscle to a single stimulus. Results: PAS-25 with 225 pairings produced a robust enhancement of corticospinal excitability, while PAS-25 with 180 pairings was less effective. Surprisingly, PAS-10 with both 180 and 225 pairings also increased excitability. Conclusions: While all four PAS paradigms enhanced M1 excitability, PAS-25 with 225 pairings induced the strongest group-level effects and was most time-efficient. Significant individual variability of PAS responses suggests that optimizing PAS parameters, including pairing number and interstimulus intervals, may be necessary for personalized approaches.